Getting Everybody to the Table : The Negotiation Process for the Regional Trade Facilitation Project in the Western Balkans - Ristic, Lazar (World Bank, Washington, DC, 2012)
The problem of our time is not how to keep nations peacefully apart, but how to bring them actively together, wrote David Mitrany in 1943. With that in mind, think about developing the concept for a regional trade facilitation project to introduce leaner and greener transit routes and simplified import and export procedures within Europe's southeastern gateways to Asia. Now, imagine representatives from the post-conflict Western Balkan region; Albania, Bosnia and Herzegovina, Croatia, Kosovo, the former Yugoslav Republic of Macedonia, Montenegro, and Serbia, all sitting around a table and agreeing on common goals for a regional trade facilitation project. Well, that is what IFC achieved during the negotiation process for such a project in the post-conflict region of the Western Balkans, a region that is moving ever closer to European Union (EU) integration but remains far away from full internal regional integration. This smart lesson describes the challenges we faced and the lessons we learned during the process of developing International Finance Corporation's (IFC's) regional trade facilitation project.